2023
DOI: 10.1155/2023/6798748
|View full text |Cite
|
Sign up to set email alerts
|

eSports Participation among Hong Kong Middle-Aged and Older Adults: A Qualitative Study

Abstract: The HK Special Administrative Region Government has been making efforts to promote active aging among older adults. This qualitative study is aimed at gaining an understanding of the perception of and experiences in eSports among middle-aged and older adults in HK, China, using the Theory of Planned Behavior. Thirty-nine adults aged >45 years were stratified by (a) whether they had experience of participating in eSports and (b) age (i.e., 45–64 years vs. ≥65 years). In addition, 10 administrators working in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…All interviews were conducted in Cantonese by the principal investigator (woman) and a research assistant (man), who were both trained in qualitative research methods, including interviewing. The interviews were based on a standard set of questions used in our previous eSports-related study [ 10 ] that had undergone pilot testing with five middle-aged and older adults. Probing questions were asked to deepen the conversation, extract key information, clarify certain matters, and use time efficiently [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…All interviews were conducted in Cantonese by the principal investigator (woman) and a research assistant (man), who were both trained in qualitative research methods, including interviewing. The interviews were based on a standard set of questions used in our previous eSports-related study [ 10 ] that had undergone pilot testing with five middle-aged and older adults. Probing questions were asked to deepen the conversation, extract key information, clarify certain matters, and use time efficiently [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…In 2018, Acer and Senior Citizen Home Safety Association held an eSports activity for older adults in HK that benefitted the participants’ health and strengthened their relationships with their families [ 8 ]. Although some studies have revealed associations between eSports and adverse health outcomes such as sleep disturbance [ 9 , 10 ], overuse strain [ 10 ], obesity [ 11 ], behavioral problems [ 12 ], sedentary behavior [ 13 ], and high levels of stress [ 14 ], others [ 10 , 15 ] have indicated that eSports can benefit physical [ 10 , 16 ], psychological [ 10 , 17 ], and social health [ 10 , 18 ]. Leung and her team also did a pilot study to examine the impact of an eight-week eSports intervention (using Fitness Boxing, Nintendo Switch) to improve the psychosocial health, physical and cognitive functions of 54 healthy older adults in 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The determinants of intention impact the individual's intentions towards the behaviour which in turn impacts the behaviour. The theory has been successful in explaining and predicting behaviours in a wide array of domains such as physical activity ( 17 ), esport ( 19 ) and smoking ( 20 ). TPB is grounded in the target behaviour, which is influenced by the strength of an individual's intention toward that behaviour.…”
Section: Theory Of Planned Behaviourmentioning
confidence: 99%